Dampak Ketersediaan Pembayaran Digital terhadap Loyalitas Pelanggan (Studi Kasus pada Pelanggan Bakso di Kab. Bandung) - Fadli Alamsyah (International Journal Administration, Business & Organization, 2023)
Digital development in this era is very rapid, giving rise to several innovations that can alleviate and facilitate various human activities. One example is digital payments. This study aims to determine the impact of the availability of digital payments on customer loyalty, especially at meatball stalls located in Kab. Bandung. The research method used in this study is a quantitative descriptive measuring tool questionnaire. A total of 135 people from Bandung Regency were involved in this research. Furthermore, data analysis will use the IBM SPSS v.25 software by examining validity and reliability tests, and simple regression analysis tests. The results of the data analysis obtained are the impact of the Availability of Digital Paymenthasng a positive and significant impact on customer loyalty.